Податок на нерухоме майно у стимулюванні економічного розвитку регіону: автореферат дис. ... канд. екон. наук : 08. 00. 08. - Аблязова, Ельвіна Зуфарівна; Аблязова, Эльвина Зуфаровна; Ablyazova, Yelvina (My University, 2017)
UK: Дисертаційну роботу присвячено обґрунтуванню теоретико-методичних засад та розробленню практичних рекомендацій щодо удосконалення порядку справляння податку на нерухоме майно, відмінне від земельної ділянки, з метою стимулювання економічного розвитку регіону. RU: Диссертационная работа посвящена обоснованию теоретических основ и разработке практических рекомендаций совершенствования порядка взыскания налога на недвижимое имущество, отличительного от земельного участка, с целью стимулирования экономического развития региона. EN: The thesis deals with the comprehensive research of theoretical essentials and practical recommendations to update the plot excluded real estate tax regulations to stimulate the regional economic development. The thesis reveals the economic essence of real estate and theoretical essentials of taxes levied on it. The author specified the economic contents of real estate and the notion as well as the notion “tax promotion of regional development” as a process of tax burden management by means of regulation of tax rates for local taxes, particularly estate ones, that will result in creation of conditions and stimuli for intensification of social and economic regional development.
Налог на недвижимое имущество в стимулировании экономического развития региона: автореф. дис. ... канд. экон. наук : 08. 00. 08
Real estate tax in stimulating the economic development of a region
Keywords: податкова система; нерухоме майно; оподаткування нерухомості; податок на нерухоме майно; соціально-економічний розвиток регіону; фінансова децентралізація; місцеві бюджети; налоговая система; недвижимое имущество; налогообложение недвижимости; налог на недвижимое имущество; социально-экономическое развитие региона; финансовая децентрализация; местные бюджеты; tax system; real estate; real estate taxation; real estate tax; social and economic regional development; financial decentralization; local budgets